Buddy Esquire and the early hip hop flyer. Issue 1 (January 2014) - Lalonde, Amanda
Abstract: Between 1978 and 1984 Buddy Esquire designed over 300 hip hop flyers. His career coincided with the first flourishing of the Bronx scene, when hip hop shifted from a community-based event to a full-blown commercial phenomenon. This paper analyses Buddy Esquire's flyer design style, supported by a discussion with the flyer artist. The analysis demonstrates that Esquire's 'neo-deco' style communicates the aspiration of live hip hop to classiness by suppressing overt graffiti elements, by alluding to the nightclub culture of disco and by using the Art Deco stylings of the Jazz Age as a signifier of sophistication. The paper then moves beyond an interpretation of the flyers, searching for reflections of Buddy Esquire's aesthetic in early hip hop culture. Finally, it proposes that Buddy Esquire's flyers challenge assumptions in current hip hop scholarship regarding early hip hop's aesthetic relationship to the past (particularly the early 20th century) and its self-documenting impulse.